Rolling Thunder - Messner, Kate; Ruth, Greg (New York : Scholastic Press, 2017)
Told in rhyming text, a boy accompanies his grandfather on the Rolling Thunder Ride for Freedom, a motorcycle parade in Washington, DC, on Memorial Day that pays tribute to American veterans.
K-3
Keywords: Motorcycling -- Fiction; Veterans -- Fiction; Grandfathers -- Fiction; Memorial Day -- Fiction; Vietnam Veterans Memorial (Washington, D.C.) -- Fiction; Stories in rhyme; Picture books